1979
DOI: 10.1051/rnd:19790211
|View full text |Cite
|
Sign up to set email alerts
|

Influence du niveau des apports énergétiques distribués à la brebis pendant la gestation sur le poids à la naissance et la croissance des agneaux

Abstract: for the lean and fat group -P < 0,100 ; 3,01 VS 3,84 kg for the low and high level -P < 0,001). Also, the growth rate of these lambs, after weaning at 6 weeks, was significantly reduced when their mothers were restricted to the maintenance level in late pregnancy (260 VS 288 g/day for the low and high level -P < 0,025).3. These effects were not observed in ewes of the autumn lambing, but lamb birth weights were usually a little lower than in spring.These results are discussed, with particular attention to seas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1981
1981
1989
1989

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…It has been shown that birth weights of twin lambs are higher during spring lambing than during autumn lambing, even if pregnant ewes received a large quantity of food (Tissier and Theriez 1979). However, Bosc et af.…”
Section: Distal Part: End Oj Gestation and Lactationmentioning
confidence: 99%
“…It has been shown that birth weights of twin lambs are higher during spring lambing than during autumn lambing, even if pregnant ewes received a large quantity of food (Tissier and Theriez 1979). However, Bosc et af.…”
Section: Distal Part: End Oj Gestation and Lactationmentioning
confidence: 99%
“…Apparent digestibility of the diets was significantly higher (P < 0.05) after tricaprylin substitution for part of the tallow. The extent of the effect increased with the level of tricaprylin (P < 0.025 (Alexander, 1974;Robinson et aL, 1977;Tissier & Theriez, 1978) (Walker & Faichney, 1964;Glimp, 1972), but medium chain triglycerides (MC! are more easily disposed of in the digestive tract of domestic newborn mammals, being readily hydrolysed in the stomach under the action of salivary lipases and partially absorbed in this organ (Leat & Harrison, 1975;Perret, 1980) and completely hydrolysed and absorbed in the intestine (Walker & Stokes, 1970;Gibney & Walker, 1977).…”
mentioning
confidence: 99%